Gerakan Sosial :Right to The City Alliance dan Revolusi Kaum Urban Menggugah Hak Atas Kota - Reski Amalia Arif (WANUA : Jurnal Hubungan Internasional, 2017)
Today, the phenomenon of globalization brings impact not only on the positive side, the seafarers have a negative side. Regarding the problem of the international regime that is more directed to the economy of capitalism, this paper raises the question of the right to the city as opposed to the development of capitalism conditions that control the world today.There have been many articles that have been discussed previously regarding the uploading of the right to the city that is considered to reject the state of capitalism and what the city's rights should be fulfilled in this regard.Two writings about Harvey and Henri Lefebvre, from the writings and ideas of these two writers set out to write about the issue of the right to the city that is now more prevalent. Given the need for a movement to aspire to the issue of the rights to this city, the writer feels the need to describe how non-state actors currently have an existence that rivals the state.The non-state actors are in the form of social movements related to the right to upload city right ie Right To The City Alliance. This movement is a social movement that is shaped as a response to urbanization in urban areas with all the impacts of urban life. Every city in the world desires a change for its sake, but the development that is carried on has caused much discrimination for the urban.This is because the city is considered as a place of dominant class competition. The eviction, discrimination of women, the homeless, and the right of ownership of the land is the result of the hegemony of capitalist knowledge. In response to the problem by appointing right to the city from Harvey's thinking and Henri Lefebvre Right to The City Alliance came into existence as an urban revolution inspired the city's right. Because the city is not only a spatial space but also a social space for the urban.